Etiological Beliefs, Treatments, Stigmatizing Attitudes toward Schizophrenia. What Do Italians and Israelis Think? - Mannarini, Stefania; Boffo, Marilisa; Rossi, Alessandro; Balottin, Laura (Frontiers in Psychology, 2018)
Background: Although scientific research on the etiology of mental disorders has improved the knowledge of biogenetic and psychosocial aspects related to the onset of mental illness, stigmatizing attitudes and behaviors are still very prevalent and pose a significant social problem. Aim: The aim of this study consists in deepening the knowledge of how attitudes toward people with mental illness are affected by specific personal beliefs and characteristics, such as culture and religion of the perceiver. More precisely the main purpose is the definition of a structure of variables, namely perceived dangerousness, social closeness, avoidance of the ill person, together with the beliefs about the best treatment to be undertaken and the sick person’ gender, able to describe the complexity of the stigma construct in particular as far as schizophrenia is concerned. Method: The study involved 305 university students, 183 from the University of Padua, Italy, and 122 from the University of Haifa, Israel. For the analyses, a LCA approach was chosen to identify a latent categorical structure accounting for the covariance between the observed variables. Such latent structure was expected to be moderated by cultural background (Italy versus Israel) and religious belief; whereas causal beliefs, recommended treatment, dangerousness, social closeness, and public avoidance were the manifest variables, namely the observed indicators of the latent variable. Results: Two sets of results were obtained. First, the relevance of the manifest variables as indicators of the hypothesized latent variable was highlighted. Second, a two-latent-class categorical dimension represented by prejudicial attitudes, causal beliefs and treatments concerning schizophrenia was found. Specifically, the differential effects of the two cultures and the religious beliefs on the latent structure and their relations highlighted the relevance of the observed variables as indicators of the expected latent variable. Conclusion: The present study contributes to the improvement of the understanding of how attitudes toward people with mental illness are affected by specific personal beliefs and characteristics of the perceiver. The definition of a structure of variables able to describe the complexity of the stigma construct in particular as far as schizophrenia is concerned, was achieved in a cross cultural perspective.